2021
DOI: 10.4081/monaldi.2021.1561
|View full text |Cite
|
Sign up to set email alerts
|

Role of awake prone positioning in patients with moderate-to-severe COVID-19: an experience from a developing country

Abstract: There is limited evidence on the efficacy of awake prone positioning (PP) in non-ventilated patients with COVID-19 who have hypoxemia. We, therefore, aim to describe our experience with the use of early proning in awake, non-intubated patients with confirmed COVID-19. In our retrospective observational study, 23 patients with confirmed positive PCR test results for Severe Acute respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and hypoxemia that required oxygen therapy with or without non-invasive ventilation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…In the present study, majority of patients were males 40 (90%). This finding was comparable to the previous some studies 11,12 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, majority of patients were males 40 (90%). This finding was comparable to the previous some studies 11,12 .…”
Section: Discussionsupporting
confidence: 93%
“…Mortality in group I was 1(4%) and in group II mortality was found 2(8%). No any severe complications were observed among both groups 11 . Proning COVID-19 has been demonstrated to lead to better oxygenation in several minor trials and hypoxemic air failure has been reported.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These findings were comparable to the previous some studies. [11,12] In our study Most of the patients 81 (81%) had bilateral lung involvement (40 in group A and 41 in group B). Interstitial infiltrates was found in 78 (40 in group A and 38 in group B) patients followed by consolidation and unilateral infiltrates.…”
Section: Discussionmentioning
confidence: 45%
“…This improves the oxygen saturation of arterial red blood cell hemoglobin (as demonstrated in the PROSERVA TRIAL). [83][84][85][86][87] General Architecture Overall, this figure is dichotomized by characterizing the features of mild and moderate COVID-19 and the interventions that comprise our regimen to prevent progression to severe disease.…”
Section: Proningmentioning
confidence: 99%